PENGATURAN ALIH FUNGSI LAHAN PERTANIAN UNTUK LAHAN PERMUKIMAN DI KABUPATEN BADUNG - Yuni Lestari, Made; Suyatna, I Nyoman (Kertha Negara : Journal Ilmu Hukum, 2014)
The titled of this research is “The Regulation of Agricultural Land Conversion toResidential Area in Badung Regency”. The method used in this research is empirical legalresearch with the statue approach, the fact approach and law concept analysis approach.There are problems which is how does the arrangement of agricultural land conversion toresidential area in Badung and what are trigger factors and inhibiting the conversion ofagricultural land to residential area in Badung Regency. The conclusion that can be drawnin this research is regulation of agricultural land conversion to residential area in Badungregency refers to Act No.26 of year 2007 about Spatial Planning, Regional RegulationProvince of Bali No.16 of year 2009 about the Regional Landscaping Plann the province ofBali, Regional Regulation of Badung Regency No. 26 of year 2013 about the RegionalLandscaping Plann the Badung Regency. That trigger factors the conversion ofagricultural land to residential area in Badung regency are legal substance factors,community factors and cultural factors while the inhibiting factors of the conversion ofagricultural land to residential area in Badung regency are law enforcer factors,equipment and facilities factors and cultural factor.
Keywords: Authority, Transfer functions, Agricultural Land, Residential Area